Content Analysis of Arabic Language Curricula in Saudi Arabia’s Elementary Stage in Light of Enhancing National Identity and Developing Skills Aligned with 21st-Century Requirements - Al-Yami, Abdullah Nasser (Journal of Curriculum and Teaching Methodology, 2025)
This study analyzes the content of Arabic language curricula for the primary stage in the Kingdom of Saudi Arabia in light of enhancing national identity and developing future skills according to the requirements of the twenty-first century. The research adopted a descriptive-analytical approach using two main tools: a content analysis checklist for the “My Beautiful Language” textbooks for upper grades (fourth, fifth, and sixth) and an electronic questionnaire administered to a sample of Arabic language teachers, with verified validity and reliability (overall reliability coefficient = 0.89). The content analysis revealed that the textbooks include multiple elements that promote national identity, with an overall frequency average of 78% of the observed indicators, particularly through texts highlighting national symbols and religious and national occasions. However, the inclusion of twenty-first-century skills—such as critical thinking, collaboration, creativity, and self-directed learning—was limited, representing only 41% of the total indicators and distributed non-systematically across the three grade levels. The integration of both national identity and future skills in the same content was rare, with combined indicators representing only 23%. The questionnaire results showed that teachers’ overall perception score regarding the importance of integrating national identity and twenty-first-century skills was 4.26 out of 5, indicating highly positive attitudes. Additionally, 87% of teachers emphasized the need to update the curriculum, while 82% stressed the importance of designing integrated learning activities that simultaneously enhance national values and global skills. The study concludes with recommendations to develop the Arabic language curricula in alignment with Saudi Vision 2030, increase the integration of national values and future skills, and empower teachers to adapt the content through modern teaching strategies that support this direction.
Keywords: National identity; future skills; Arabic language curricula; primary stage; Saudi Vision 2030